2021
DOI: 10.1515/dx-2020-0160
|View full text |Cite
|
Sign up to set email alerts
|

Use of a structured approach and virtual simulation practice to improve diagnostic reasoning

Abstract: Objectives In 2015, the National Academy of Medicine IOM estimated that 12 million patients were misdiagnosed annually. This suggests that despite prolonged training in medical school and residency there remains a need to improve diagnostic reasoning education. This study evaluates a new approach. Methods A total of 285 medical students were enrolled in this 8 center, IRB approved trial. Students were randomized to receive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education. Moreover, only one third of (31) articles ( 15 , 16 , 22 , 26 , 31 33 , 38 , 47 , 48 , 52 , 53 , 56 , 58 , 60 – 62 , 64 , 65 , 67 , 71 , 73 , 75 , 76 , 78 80 , 95 , 96 , 101 , 105 ) included in this review were based on the commercially available or free VS softwares/platforms, the rest used the self-developed ones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the process, multimedia elements add authenticity to the VP scenario. Overall, several studies indicated that VPs have the potential to train students in clinical reasoning [7][8][9].…”
Section: Introductionmentioning
confidence: 99%